Answer:
<h2>g = 17</h2>
Step-by-step explanation:
15 less than twice a number g is 19
2g - 15 = 19 <em>add 15 to both sides</em>
2g - 15 + 15 = 19 + 15
2g = 34 <em>divdie both sides by 2</em>
2g : 2 = 34 : 2
g = 17
Answer:
Part A: Option 2, A: Anna’s answer is incorrect. She correctly factored out 5x, but incorrectly identified a and b, so her answer cannot be correct.
Part B: Option 3, B: 5x(x+2)(x^2−2x+4)
Step-by-step explanation:
p(x) = 5x^4 + 40x
p(x) = 5x(x^3 + 8)
p(x) = 5x(x + 2)(x^2 - 2x + 4)
Part A: Option 2, A: Anna’s answer is incorrect. She correctly factored out 5x, but incorrectly identified a and b, so her answer cannot be correct.
Part B: Option 3, B: 5x(x+2)(x^2−2x+4)
Answer:
D.
Step-by-step explanation:
h(x)=f(x)g(x) means multiply the expression for f to the expression for g.
That is the problem is just asking you to do (11x-5)(-2x-4).
Let's use foil.
First: 11x(-2x)=-22x^2
Outer: 11x(-4)=-44x
Inner: -5(-2x)=10x
Last: -5(-4)=20
------------------------Add together!
-22x^2-34x+20
D.
Answer: 17/22
Step-by-step explanation: